Family Support of Third-Grade Reading Skills, Motivation, and Habits - Lauren Capotosto; James S. Kim; Mary A. Burkhauser; Soojin Oh Park; Bethany Mulimbi; Maleka Donaldson; Helen Chen Kingston (SAGE Publishing, 2017)
This qualitative study investigated the ways in which 84 parents from predominantly low-income communities described supporting their third graders' reading skills, motivation, and habits. Thematic analysis of open-ended parent interviews indicated that parents actively and deliberately scaffolded their children's progress toward developing independent reading skills. Parents explicitly communicated the value of reading in everyday conversations; actively listened to their children read, even if they did not understand the language in which the text was written; asked reading comprehension questions; created a home environment conducive to sustained reading; promoted reader autonomy through encouragement of strategy use; and incorporated reading practices into daily routines. Parents often described their own efforts as responsive to their children's level of reading motivation and reading performance, thus highlighting the reciprocal nature of parent-child reading interactions. Findings reveal a variety of ways in which families support their children's reading skills, motivation, and habits.